Prescription attitudes and practices regarding clozapine among Serbian psychiatrists: results of a nationwide survey. (May 2021) - Ignjatovic Ristic, Dragana; Cohen, Dan; Ristic, Ivan
Objective: Despite clozapine being the most effective treatment for treatment-resistant schizophrenia (TRS), a clear explanation as to why it is underutilized and why its initiation is delayed remains unclear. The first aim of the study was to conduct a nation-wide assessment of both the psychiatrists' attitudes of the obstacles for prescribing clozapine as well as their prescription practices. The second aim was to make recommendations, based on the results obtained, for improving the Serbian clozapine guidelines. Methods: A questionnaire was conducted consisting of two parts. One regarded the clinical characteristics of the psychiatrists, while the second contained questions about indications for clozapine initiation, clozapine prescribing tendencies, and barriers to clozapine use. The questionnaire was sent to 302 Serbian psychiatrists. Results: With 161 out of the 302 psychiatrists returning the questionnaires, the response rate was 53.3%. Nearly 60% of the psychiatrists treated 10 or more patients with clozapine, with TRS being the most common indication. Only four psychiatrists (2.5%) had no patients currently on clozapine. Psychiatrists indicated that their fear of agranulocytosis (68%) constituted the greatest obstacle for clozapine prescription, followed closely by weight gain (56%), and sedation (39%). Despite their fear of agranulocytosis, only 83.9% of the psychiatrists monitored leukocytes regularly. Conclusion: In general, psychiatrists in Serbia seem to be confident in prescribing clozapine, even in the absence of clear monitoring guidelines and the possibility of therapeutic drug monitoring. In order to reduce obstacles for clozapine prescription, monitoring laxity, and an overreliance on personal experience, we recommend three modifications of the existing clozapine guideline.